Chemical optimization of macrocyclic HIV-1 inactivators for improving potency and increasing the structural diversity at the triazole ring. Issue 37 (3rd August 2017) - Rashad, Adel A.; Acharya, Kriti; Haftl, Ann; Aneja, Rachna; Dick, Alexej; Holmes, Andrew P.; Chaiken, Irwin
Abstract : HIV-1 entry inhibition remains an urgent need for AIDS drug discovery. cPTs belong to a class of entry inhibitors that block Env binding to cellular receptors and trigger Env-gp120 shedding. Abstract : HIV-1 entry inhibition remains an urgent need for AIDS drug discovery and development. We previously reported the discovery of cyclic peptide triazoles (cPTs) that retain the HIV-1 irreversible inactivation functions of the parent linear peptides (PTs) and have massively increased proteolytic resistance. Here, in an initial structure–activity relationship investigation, we evaluated the effects of variations in key structural and functional components of the cPT scaffold in order to produce a platform for developing next-generation cPTs. Some structural elements, including stereochemistry around the cyclization residues and Ile and Trp side chains in the gp120-binding pharmacophore, exhibited relatively low tolerance for change, reflecting the importance of these components for function. In contrast, in the pharmacophore-central triazole position, the ferrocene moiety could be successfully replaced with smaller aromatic rings, where a p -methyl-phenyl methylene moiety gave cPT24 with an IC50 value of 180 nM. Based on the observed activity of the biphenyl moiety when installed on the triazole ring (cPT23, IC50 ∼ 269 nM), we further developed a new on-resin synthetic method to easily access the bi-aryl system during cPT synthesis, in good yields. A thiophene-containing cPT AAR029N2 (36 ) showed enhanced entropically favored binding to Env gp120 and improved antiviral activity (IC50 ∼ 100 nM) compared to the ferrocene-containing analogue. This study thus provides a crucial expansion of chemical space in the pharmacophore to use as a starting point, along with other allowable structural changes, to guide future optimization and minimization for this important class of HIV-1 killing agents.